Pengaruh Profitabilitas, Leverage dan Likuiditas terhadap Return Saham Perusahaan Manufaktur di Bursa Efek Indonesia - Milna Dwi Lestari; Nina Karina Karim; Robith Hudaya (Riset, Ekonomi, Akuntansi dan Perpajakan (Rekan), 2022)
This study aims to determine the effect of profitability, leverage and liquidity on stock returns. The test was carried out on 14 samples of food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2015–2019 period. This type of research is associative with a quantitative approach using data sources in the form of financial reports obtained from the official website of the Indonesia Stock Exchange (IDX). The data was processed using the Statistical Product and Service Solutions (SPSS) software version 23.0. The results of this study are profitability measured using Return On Assets (ROA) has no effect on stock returns, leverage as measured using Debt to Equity Ratio (DER) has no effect on stock returns and liquidity as measured using Current Ratio (CR) has no effect on stock returns